Effects of oleic acid on the biosynthesis of lipoprotein apoproteins and distribution into the very-low-density lipoprotein by the isolated perfused rat liver. - Salam, W H (1988)
The effects of oleic acid on the biosynthesis and secretion of VLDL (very-low-density-lipoprotein) apoproteins and lipids were investigated in isolated perfused rat liver. Protein synthesis was measured by the incorporation of L-[4,5-3H]leucine into the VLDL apoproteins (d less than 1.006) and into apolipoproteins of the whole perfusate (d less than 1.21). Oleate did not affect incorporation of [3H]leucine into total-perfusate or hepatic protein. The infusion of oleate, however, increased the mass and radioactivity of the VLDL apoprotein in proportion to the concentration of oleate infused. Uptake of oleate was similar with livers from fed or fasted animals. Fasting itself (24 h) decreased the net secretion and incorporation of [3H]leucine into total VLDL apoprotein and decreased the output of VLDL protein by the liver. A linear relationship existed between the output of VLDL triacylglycerol (mumol/h per g of liver) and secretion and/or synthesis of VLDL protein. Net output of VLDL cholesterol and phospholipid also increased linearly with VLDL-triacylglycerol output. Oleate stimulated incorporation of [3H]leucine into VLDL apo (apolipoprotein) E and apo C by livers from fed animals, and into VLDL apo Bh, B1, E and C by livers from fasted rats. The incorporation of [3H]leucine into individual apolipoproteins of the total perfusate lipoprotein (d less than 1.210 ultracentrifugal fraction) was not changed significantly by oleate during perfusion of livers from fed rats, suggesting that the synthesis de novo of each apolipoprotein was not stimulated by oleate. This is in contrast with that observed with livers from fasted rats, in which the synthesis of the total-perfusate lipoprotein (d less than 1.210 fraction) apo B, E and C was apparently stimulated by oleate. The observations with livers from fed rats suggest redistribution of radioactive apolipoproteins to the VLDL during or after the process of secretion, rather than an increase of apoprotein synthesis de novo. It appears, however, that the biosynthesis of apo B1, Bh, E and C was stimulated by oleic acid in livers from fasted rats. Since the incorporations of [3H]leucine into the VLDL and total-perfusate apolipoproteins were increased in fasted-rat liver when the fatty acid was infused, part of the apparent stimulated synthesis of the VLDL apoprotein may be in response to the increased formation and secretion of VLDL lipid.